High speed antimony-based superlattice photodetectors transferred on sapphire. (17th October 2019) - Dehzangi, Arash; McClintock, Ryan; Wu, Donghai; Li, Jiakai; Johnson, Stephen M.; Dial, Emily; Razeghi, Manijeh
Abstract: We report the substrate transfer of InAs/GaSb/AlSb based type-II superlattice (T2SL) e-SWIR photodetector from native GaSb substrates to low-loss sapphire substrate in order to enhance the frequency response of the device. We have demonstrated the damage-free transfer of T2SL-based thin-films to sapphire substrate using top–down processing and a chemical epilayer release technique. After transfer the −3 dB cut-off frequency increased from 6.4 GHz to 17.2 GHz, for 8  μ m diameter circular mesas under −15 V applied bias. We also investigated the cut-off frequency verses applied bias and lateral scaling to assess the limitations for even higher frequency performance.